The use of information technology for training construction workers in reading and interpreting plans - Cattani, Airton (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Current information and communication technologies offer a multitude of possibilities when applied to education. However, such technologies are usually employed in teaching/learning environments (schools, universities, research and education centres), and are employed by users whose main activity is studying. The aim of this study is to indicate the possibilities offered by telematics as a tool for training construction workers, for whom access to these resources is not usually easy. Using an interdisciplinary approach involving architecture, engineering, education, psychology, and computer science, it presents the theoretical principles and the results obtained from an experiment in which a web site for training construction workers in reading and interpreting architectural drawings was developed.